Αναζήτηση Εικόνες Χάρτες Play YouTube Ειδήσεις Gmail Drive Περισσότερα »
Είσοδος
 Βιβλία Βιβλία The square of the difference of two quantities is equal to the square of the first minus twice the product of the first by the second, plus the square of the second. The Elements of Algebra - Σελίδα 75
των Elias Loomis - 1856 - 268 σελίδες
Πλήρης προβολή - Σχετικά με αυτό το βιβλίο ## Elements of Algebra: Tr. from the French of M.Bourdon. Revised and Adapted ...

Charles Davies - 1835 - 353 σελίδες
...(a-by=(ab) (ab)=a1-2ab+V That is, the square of the difference between two quantities is composed of the square of the first, minus twice the product of the first by the second, plus the square of the second. Thus, (7a3i3-12ai3)3=49aW-168a''is+144a3ii1. 3d. Let... ## A New Introduction to the Science of Algebra...

Silas Totten - 1836 - 304 σελίδες
...adding them together : thus, and 36aV + 60a3^3 + 25aix3 = (Sax2 + 5aV)2, or x X (6ax2 + 5aV). . 2. The square of the difference of two quantities is equal to the sum of their squares, minus twice their product. Let a be the greater of two quantities, and b the... ## Elements of Algebra

1838 - 358 σελίδες
...difference, a — b, we have (a-by=(ab) (ab)=a?-2ab+t2 : That is, the square of the difference between two quantities is equal to the square of the first, minus twice the product of the frst by the second, plus the square of the second. Thus, fTVi2— 12ai3)2=49a4i4— 168a3i5+144a2i6.... ## The British Cyclopaedia of the Arts, Sciences, History, Geography ...

...twice the product of the first and second. 2°. That (o — b) (a — i) = a* — 2o6 + V ; or, that the square of the difference of two quantities is equal to the square of the first, plug the square of the second, minus twice the product of the first and second. 3°. That (a + i) (a... ## First Lessons in Algebra: Embracing the Elements of the Science

Charles Davies - 1839 - 252 σελίδες
...39. To form the square of a difference a— b, we have That is, the square of the difference between two quantities is equal to the square of the first, minus twice the product of the first by the second, plus the square of the second. 1 Form the square of 2a — b. We have 2. Form the square... ## Elements of Algebra

Bourdon (M., Louis Pierre Marie) - 1839 - 324 σελίδες
...difference, a — b, we have (a— 6)2=(a-6) (a-6)=a2-2a6 + 62: That is, the square of the difference between two quantities is equal to the square of the first, minus twice the product of the first by the second, plus the square of the second. Thus, (7a262— 12a63)2=49a4M— 168a365+144a266. 3d.... ## First Lessons in Algebra: Embracing the Elements of the Science

Charles Davies - 1840 - 252 σελίδες
...39. To form the square of a difference a— b, we have That is, the square of the difference between two quantities is equal to the square of the first, minus twice the product of tht frst by the second, plus the square of the second. 1 Form the square of 2<z— b. We have (2a —... ## Elementary Algebra: Embracing the First Principles of the Science

Charles Davies - 1842 - 258 σελίδες
...a— b, we have (a—b)2 = (a—b) (a—b)—az~2ab+bz. That is, the square of the difference between two quantities is equal to the square of the first, minus twice the product of the first by the second, plus the square of the second, 1. Form the square of 2a— b. We have (2a—6)2=4o2—4a6+62.... ## Elements of Algebra

Charles Davies - 1842 - 358 σελίδες
...difference, a—b, we have (a—b)2=(ab) (ai)=a 2 —2ai+i2: That is, the square of the difference between two quantities is equal to the square of the first, minus twice the product of the first by the second, plus the square of the second. Thus, (7o 2 i2—12ai 3 ) 2 =49a 4 i 4 —168a 3 i 6... ## An Elementary Treatise on Algebra: Designed to Facilitate the Comprehension ...

Ormsby MacKnight Mitchel - 1845 - 294 σελίδες
...second. 17. Multiply a — b by a — b. The product is a2 — 2a6+62 ; from which we perceive, that the square of the difference of two quantities, is...of the first minus twice the product of the first by the second, plus the square of the second. 18. Multiply a+b by a — b. The product is a2 — b2...